Nursing care as a predictor of phlebitis related to insertion of a peripheral venous cannula in emergency departments: findings from a prospective study. Issue 3 (March 2016) - Palese, A.; Ambrosi, E.; Fabris, F.; Guarnier, A.; Barelli, P.; Zambiasi, P.; Allegrini, E.; Bazoli, L.; Casson, P.; Marin, M.; Padovan, M.; Picogna, M.; et al.
Summary: Background: To date, few studies have investigated the occurrence of phlebitis related to insertion of a peripheral venous cannula (PVC) in an emergency department (ED). Aim: To describe the natural history of ED-inserted PVC site use; the occurrence and severity of PVC-related phlebitis; and associations with patient, PVC and nursing care factors. Methods: A prospective study was undertaken of 1262 patients treated as urgent cases in EDs who remained in a medical unit for at least 24 h. The first PVC inserted was observed daily until its removal; phlebitis was measured using the Visual Infusion Phlebitis Scale. Data on patient, PVC, nursing care and organizational variables were collected, and a time-to-event analysis was performed. Findings: The prevalence of PVC-related phlebitis was 31%. The cumulative incidence (78/391) was almost 20% three days after insertion, and reached >50% (231/391) five days after insertion. Being in a specialized hospital [hazard ratio (HR) 0.583, 95% confidence interval (CI) 0.366–0.928] and receiving more nursing care (HR 0.988, 95% CI 0.983–0.993) were protective against PVC-related phlebitis at all time points. Missed nursing care increased the incidence of PVC-related phlebitis by approximately 4% (HR 1.038, 95% CI 1.001–1.077). Conclusions: Missed nursing care and expertise of the nurses caring for the patient after PVC insertion affected the incidence of phlebitis; receiving more nursing care and being in a specialized hospital were associated with lower risk of PVC-related phlebitis. These are modifiable risk factors of phlebitis, suggesting areas for intervention at both hospital and unit level.